Ślązacy Cieszyńscy jako „nasi–Obcy” / „my–Inni” w pismach Jana Szczepańskiego - Szkaradnik, Katarzyna (Kultura i Społeczeństwo, 2016)
The aim of this article is to reconstruct and interpret the vision of Silesians as Others contained in the texts of the sociologist Jan Szczepański. The article begins by pointing out Silesia’s lack of homogeneity and complex relation with Poland, as well as Szczepański’s predominant identiﬁcation of Silesia with his native Cieszyń and his mythologizing of it as a borderland mainstay of Polishness. In this context, there is a clear parallel in Szczepański’s writings between Silesians and Indians (that is, the maintenance of a separate culture by the autochthonous people in spite of efforts to discourage their otherness). At the same time, Szczepański shows the culture of Cieszyń to be different from the dominant Polish model, being based mainly on values connected with the Protestant ethos: industry, reliability, order, and rationality. The author explains how presentation of an idealized Cieszyń community emerges in Szczepański’s writings as the project of ‘becoming another’, a path toward understanding one’s own cultural roots in order to use them creatively to shape real conditions.